2006
DOI: 10.1529/biophysj.105.069013
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Calcium Entry at the T-Tubules and Surface Membrane in Rat Ventricular Myocytes

Abstract: The action potential of cardiac ventricular myocytes is characterized by its long duration, mainly due to Ca flux through L-type Ca channels. Ca entry also serves to trigger the release of Ca from the sarcoplasmic reticulum. The aim of this study was to investigate the role of cell membrane invaginations called transverse (T)-tubules in determining Ca influx and action potential duration in cardiac ventricular myocytes. We used the whole cell patch clamp technique to record electrophysiological activity in int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 57 publications
(75 reference statements)
8
68
0
Order By: Relevance
“…Consistent with this, it has been shown that the peripheral VOCC/RyR couplings in ventricular myocytes are functionally distinct from their T-tubule-located counterparts. They may be less well arranged for EC-coupling, but provide more Ca 2+ influx during depolarisation for SR reloading [35,36]. It therefore appears that following detubulation, ventricular myocytes rely on relatively weaker VOCC/RyR couplings in their periphery, as compared to the deliberate physiological peripheral VOCC/RyR couplings of atrial myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, it has been shown that the peripheral VOCC/RyR couplings in ventricular myocytes are functionally distinct from their T-tubule-located counterparts. They may be less well arranged for EC-coupling, but provide more Ca 2+ influx during depolarisation for SR reloading [35,36]. It therefore appears that following detubulation, ventricular myocytes rely on relatively weaker VOCC/RyR couplings in their periphery, as compared to the deliberate physiological peripheral VOCC/RyR couplings of atrial myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell pellets were collected by centrifugation and resuspended in 0.5 ml PBS. 15 Then, 0.5 ml of propidium iodide solution (100 mg ml À1 in PBS) was added and the mixture was allowed to stand on ice for 30 min. The myocardial cells (1Â10 6 ml À1 ) were analyzed with a FACScan flow cytometer (Becton Dickinson, San Jose, CA, USA) and distribution of the cell cycle phases was determined by means of ModFit LT software (Verity Software House, Topsham, ME, USA).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…It is thus not surprising that reducing NP o rapidly reduces the fraction of active junctions from the relatively large value at V m ϭ0 mV (Figure 6a). We did not study the Ϸ30% of LCCs on the surface sarcolemma, 32 but these likely also colocalize with RyRs at surface junctions. 5 Although Brette et al 32,33 measured slower I Ca inactivation for surface versus transverse tubular I Ca , they reported similar ECC gain for both.…”
Section: Np O and Cicr Gainmentioning
confidence: 99%